Inflammatory bowel disease and associated cardiovascular disease outcomes: A systematic review. Issue 6 (10th February 2023) - Jaiswal, Vikash; Batra, Nitya; Dagar, Mehak; Butey, Swatika; Huang, Helen; Chia, Jia Ee; Naz, Sidra; Endurance, Evbayekha O.; Raj, Nishchita; Patel, Srushti; Maroo, Dipansha; Ang, Song Peng; et al.
Abstract : Background: There is limited and conflicting data available regarding the cardiovascular disease outcomes associated with inflammatory bowel disease (IBD). Objective: We aim to perform a systematic review to evaluate the cardiovascular outcomes and mortality associated with IBD patients. Methods: A systematic literature search has been performed on PubMed, Embase, Cochrane, and Scopus from inception till May 2022 without any language restrictions. Results: A total of 2, 029, 941 patients were included in the analysis from 16 studies. The mean age of the patients was 45.6 years. More females were found compared with males (57% vs 43%). The most common risk factors for cardiovascular disease (CVD) included smoking (24.19%) and alcohol (4.60%). The most common comorbidities includes hypertension (30%), diabetes mellitus (14.41%), dyslipidemia (18.42%), previous CVD (22%), and renal disease (10%). Among outcomes, all-cause mortality among IBD patients was 1.66%; ulcerative colitis (UC): 15.92%; and Crohn disease (CD): 0.30%. Myocardial Infarction (MI) among IBD patients were 1.47%, UC: 30.96%; and CD: 34.14%. CVD events among IBD patients were 1.95%. Heart failure events among IBD patients were 5.49%, stroke events among IBD patients were 0.95%, UC: 2.63%, and CD: 2.41%, respectively. Conclusion: IBD patients are at higher risk for adverse cardiovascular outcomes, especially in women. Although there remains a lack of concrete treatment algorithms and assessment parameters that better characterize IBD risk factors, nutritional modifications and physical activity should be at the forefront of CVD prevention in IBD.